USP47 Promotes Tumorigenesis by Negative Regulation of p53 through Deubiquitinating Ribosomal Protein S2 - Cho, Jinhong; Park, Jinyoung; Shin, Sang Chul; Jang, Mihue; Kim, Jae-Hong; Kim, Eunice EunKyeong; Song, Eun Joo (MDPI, 2020)
p53 is activated in response to cellular stresses such as DNA damage, oxidative stress, and especially ribosomal stress. Although the regulations of p53 by E3 ligase and deubiquitinating enzymes (DUBs) have been described, the cellular roles of DUB associated with ribosomal stress have not been well studied. In this study, we report that Ubiquitin Specific Protease 47 (USP47) functions as an important regulator of p53. We show that ubiquitinated ribosomal protein S2 (RPS2) by Mouse double minute 2 homolog (MDM2) is deubiquitinated by USP47. USP47 inhibits the interaction between RPS2 and MDM2 thereby alleviating RPS2-mediated suppression of MDM2 under normal conditions. However, dissociation of USP47 leads to RPS2 binding to MDM2, which is required for the suppression of MDM2, consequently inducing up-regulation of the p53 level under ribosomal stress. Finally, we show that depletion of USP47 induces p53 and therefore inhibits cell proliferation, colony formation, and tumor progression in cancer cell lines and a mouse xenograft model. These findings suggest that USP47 could be a potential therapeutic target for cancer.
Keywords: ENZYME; PATHWAY; MDM2; ACTIVATION; CANCER; UBIQUITINATION; BIOGENESIS; INHIBITORS; STABILITY; APOPTOSIS